2010
DOI: 10.1002/lary.21127
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic factors affect surgical outcomes in allergic fungal sinusitis

Abstract: Epidemiologic factors may play an important role in the presentation and progression as well as in surgical outcomes of patients diagnosed with allergic fungal sinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 9 publications
0
18
0
2
Order By: Relevance
“…The incidence of invasive fungal sinusitis has undergone a steep rise in recent years (Ponikau et al, 1999;Riechelmann, 2011;Champagne et al, 2010;Karthikeyan and Nirmal Coumare, 2010;Naghibzadeh et al, 2011). Indeed, fungal sinusitis commonly occurs in immunocompromised patients; however, more and more cases occur in patients without immunodeficiencies, which is an alarming trend.…”
Section: Discussionmentioning
confidence: 95%
“…The incidence of invasive fungal sinusitis has undergone a steep rise in recent years (Ponikau et al, 1999;Riechelmann, 2011;Champagne et al, 2010;Karthikeyan and Nirmal Coumare, 2010;Naghibzadeh et al, 2011). Indeed, fungal sinusitis commonly occurs in immunocompromised patients; however, more and more cases occur in patients without immunodeficiencies, which is an alarming trend.…”
Section: Discussionmentioning
confidence: 95%
“…The Lund-Kennedy nasal endoscopy scoring system grades sinonasal disease by assigning a numerical value to the presence of polyps, discharge, scarring, edema, and crusting. Each sinonasal cavity is graded separately, and they are then combined to obtain an overall endoscopy score [23,24]. The postoperative follow-up visits last over 12 months after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…30 Champagne et al showed improvements in quality of life and endoscopy scores in all patient groups at 12 months follow-up. 31 In this series, all patients were treated postoperatively with saline irrigations, topical nasal steroid spray, oral antibiotics and a 1-month oral steroid taper. Their maintenance treatment consisted of topical nasal steroid spray, nasal saline, montelukast, budesonide irrigations, and month-long bursts of oral steroids for exacerbations.…”
Section: Managementmentioning
confidence: 99%